El talento humano y su incidencia en el desempeño laboral en el Ministerio de Inclusión Económica y Social (MIES), en la ciudad de Guaranda provincia Bolívar, año 2023. - Pilamunga Chimborazo, Nathaly Marisol (2024)
Human talent management, in any type of organization, plays an important role in job performance, in order to achieve institutional objectives. Considering that their job is to maintain a balance between employees and employers. This research was developed in order to know how the management of human talent carried out by the company affects the work performance of its collaborators. This research work is composed as follows: In Chapter I, there is the problem, the objectives, of the research, which is focused on determining how human talent affects the work performance of the MIES of Guaranda, considering that human talent plays an important role within the institutions. The second chapter stipulates the theoretical, legal, scientific and conceptual framework, where in the legal framework the laws and regulations that govern the MIES are considered, in the scientific framework theoretical aspects expressed by several authors, on the management of human talent, its importance, objectives and its impact on the work performance of its collaborators. Chapter 3 contains the type of research, which has a qualitative approach, applying descriptive, explanatory, field and bibliographic research, with the aim of finding the particularities that the organization has so that it is reflected in work performance. The survey was applied to the employees and the interview to the authority. Chapter 4 The proposal is where a strategy plan is proposed that allows us to improve the work performance of workers.